A Swot Analysis of AI – Powered Chatbots in English Language Education - Hijayadi, Ramdani; Jamilah (PT FORMOSA CENDEKIA GLOBAL, 2024)
An essential tool for businesses to evaluate their position in the market and handle unpredictable times is a SWOT analysis. It looks at four key elements: the strengths, weaknesses, opportunities, and threats of using AI-powered chatbots in educational settings. 14 students were chosen for the qualitative descriptive based on their prior interactions with chatbots driven by artificial intelligence. Open-ended questions from an interview guide were used in semi-structured interviews to learn more about participants’ perceptions, experiences, and difficulties using AI-powered chatbots. Following ethical study norms, digital voice recorders were utilized to guarantee precise transcription and analysis while protecting participant privacy and confidentiality. To learn more about the experiences and viewpoints of the participants, this method entailed finding, examining, and summarizing patterns or themes in the data collection. Significant strengths of AI-powered chatbots in the educational context include quick and tailored replies, improved accessibility, and ongoing assistance. They encourage self-directed learning and increase learning efficiency. Nonetheless, difficulties include managing intricate inquiries, a lack of empathy, an excessive dependence on technology, and worries over data security and privacy. Maximizing the promise of AI-powered chatbots while addressing their limits to enhance instructional practice and results requires striking a balance between these strengths and weaknesses